Pengaruh leverage dan Struktur Modal terhadap Nilai Perusahaan: Peran Kebijakan Dividen sebagai Variabel Moderasi pada Sektor Consumer Cyclicals - Della Puspita; Endah Prawesti Ningrum; Tri Yulaeli (Jurnal Kendali Akuntansi, 2026)
This study aims to examine the effect of leverage and capital structure on firm value, with dividend policy serving as a moderating variable, in consumer cyclicals companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative research approach using secondary data obtained from companies’ annual reports and financial statements. Purposive sampling was applied to select the research sample, resulting in 25 companies with a total of 125 firm-year observations. Data analysis was conducted using panel data regression and Moderated Regression Analysis (MRA) with EViews 12 software. The results indicate that leverage has a positive and significant effect on firm value, suggesting that an optimal level of debt can enhance investor confidence and increase corporate value. In contrast, capital structure does not have a significant effect on firm value. Furthermore, dividend policy positively and significantly strengthens the relationship between leverage and firm value, while negatively and significantly weakening the relationship between capital structure and firm value. These findings imply that dividend policy plays an important moderating role in corporate financial decisions and provides valuable insights for managers, investors, and policymakers in optimizing financing strategies to enhance firm value and maintain long-term corporate sustainability.